Social Criteria of Young People's Environmental Responsibility - Irina V. Tsvetkova; Tatyana N. Ivanova (National Research Mordova State University, 2017)
Introduction: the article deals with the process of nurturing environmental responsibility among young people. The challenge of environmental responsibility is correlated with ensuring national environmental security and implementing methods of sustainable development of society. The timeliness of the research lies in defining a system of criteria for the environmental responsibility among young people. These methods contribute to the formation of an integrated approach to the organisation of environmental education and upbringing. The purpose of this article is to test hypotheses about the differences of structure and levels of environmental responsibility of students, depending on speciali zation training. Materials and Methods: empirical basis of research was based on the survey of students at higher education institutions of Togliatti. Questionnaire method gives an opportunity to reveal the opinions of students of various specialisations of environmental responsibility and to establish differences between groups of respondents. Results: students of different specialisations have different levels of axiological, cognitive and activity components in the structure of environmental responsibility: the value aspect prevails over cognitive and activity aspects. The authors found significant differences in the cognitive component of environmental responsibility in environmental students compared to students of other specialisations. The activity component in two groups is hardly developed. It testifies to the lack of an integrated approach to environmental education and upbringing in universities. Discussion and Conclusions: environmental responsibility in the minds of modern young people is usually associated with common worldview categories than with practical actions. This is typical view for all students, regardless of the specialisation. The results of the study can be applied to the criteria of environmental responsibility to improve the effectiveness of environmental education.